2017
DOI: 10.4314/ahs.v16i4.5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of factors affecting energy intake of adolescent girls

Abstract: Background: Adolescence is considered a critical period marked by an increase in energy intake to meet the body's physiological needs especially during puberty. This study reviews existing literature and critically analyses factors associated with eating habits and energy intake of adolescent girls. Methods: A comprehensive search was conducted to identify at least 200 peer reviewed articles which dealt with the factors affecting energy intake (EI) and eating habits of adolescent girls. Studies were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 85 publications
0
13
0
2
Order By: Relevance
“…The previous systematic review also revealed that many other factors such as PA level, socioeconomic status (SES), diet, individual and social factors contribute to either a higher or a lower energy intake among adolescents [52]. In regards to such factors, this review only found weak evidence for the relation between ethnicity and eating and meal skipping behaviours.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The previous systematic review also revealed that many other factors such as PA level, socioeconomic status (SES), diet, individual and social factors contribute to either a higher or a lower energy intake among adolescents [52]. In regards to such factors, this review only found weak evidence for the relation between ethnicity and eating and meal skipping behaviours.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with a previous systematic review, which reported that most girls had a desire to be thin as they perceived that a thin figure is the ideal female body image. It also found that girls had higher nutrition knowledge scores than boys, particularly because girls were more likely to read nutritional food labels [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past two decades, Lebanon has experienced significant changes in its socio-cultural norms, alleviating some of the cultural barriers that young girls used to face such as the negative connotations associated with going out and participating in social activities (45) . These changes may have contributed to the fostering of modern 'westernised' habits among young girls, such as eating out in restaurants and fast food chains, which may at least partly explain the consistent temporal decrease in MD adherence among Lebanese girls (46) .…”
Section: Discussionmentioning
confidence: 99%
“…Puberty is the rst stage of adolescence and is among the possible challenges in this period. The physical changes during puberty can affect mental, behavioral, and social performances of adolescents [2]. Puberty is one of the time periods in which there is the highest risk for behavioral, social and sexual problems [3].…”
Section: Introductionmentioning
confidence: 99%